Interpretable MOOC dropout prediction using different Ensemble Methods and XAI - Khan, Labib Hasan; Haque, Mohammed Ashfaqul; Ibrahim, Esaba Ahnaf (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.